Comparative study of TKPN test results based on gender among high school students in jambi province - Krisvoniawati Hidayah; Nabil Afiqra Febriza; Muhammad Fathan Arisyi; Herudi Lubis; Alek Oktadinata; Ely Yuliawan (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2025)
Problems: Differences in physical fitness based on gender are often reported, but variations between schools as a contextual factor in learning readiness have not been empirically explored at the high school level. This study examines these differences by considering the influence of school institutions. Purpose: To analyze differences in the results of the Nusantara Student Fitness Test (TKPN) based on gender and inter-school variations among high school students in Jambi Province. Methods: A comparative quantitative study with a cross-sectional design using data from 85 students (35 male, 50 female) in three high schools. The TKPN components included flexibility, abdominal muscle endurance, leg-arm muscle endurance, and cardiovascular endurance. Statistical analysis used Welch's t-test and two-way ANOVA (gender × school). Results: There was no significant difference in PFT composite scores between males (10.68±1.39) and females (10.74±2.27) (p=0.879). The effect of gender on each component was also insignificant (p>0.05). However, a strong school effect was found on the composite score (F=18.07; p<0.001; ηp²=0.33), with the highest mean at SMAN 5 Kota Jambi (11.97±1.35). Conclusion: Differences in fitness based on gender in this sample were not significant, while variations between schools showed an important contextual influence. This study has limitations in its generalizability due to the limited sample size. The contribution of this study provides an empirical basis for the development of school-based fitness interventions. Suggestions for future research include expanding the sample size and investigating specific school factors such as the quality of facilities and physical education learning.